Evaluación del factor de condición (k) en litopenaeus vannamei alimentado con harina de acheta domesticus (grillo) - Zambrano Leon, Nelson Javier; Gallo Mendieta, Geovanny Steeven (Machala : Universidad Técnica de Machala, 2025)
This study aimed to evaluate the effect of including domestic cricket meal (Acheta domesticus) as a partial replacement for fishmeal in the diet of Pacific white shrimp (Litopenaeus vannamei), focusing specifically on its influence on the condition factor (K), an indicator of the organism’s physiological status. Four isoproteic experimental diets were formulated with inclusion levels of 0% (control), 12%, 22%, and 32% cricket meal, and were administered over an eight-week period to juvenile L. vannamei, which were fed three times daily—at 06:00, 12:00, and 17:00—with a ration equivalent to 5% of their biomass. Growth parameters (weight and length) were recorded weekly, and the condition factor was calculated for each individual. The results indicated that weight and length gain were negatively affected by suboptimal conditions, such as high stocking density (70 shrimp/m²) and declining water temperature, both of which acted as limiting factors across all treatments. Although the treatment with 32% inclusion (TR3) exhibited slightly higher and more stable K values, no statistically significant differences were observed compared to the control, limiting the evidence of any physiological benefit from Acheta domesticus under the conditions tested. Therefore, while cricket meal presents a functionally adequate protein source with a suitable nutritional profile, its inclusion in aquafeeds did not significantly enhance physiological or productive performance under environmental stress, and its use is recommended only in systems that ensure optimal culture conditions.
El presente estudio tuvo como objetivo evaluar el efecto de la inclusión de harina de grillo doméstico (Acheta domesticus) como sustituto parcial de la harina de pescado en la dieta del camarón blanco del Pacífico (Litopenaeus vannamei), enfocándose particularmente en su influencia sobre el factor de condición (K), un indicador del estado fisiológico del organismo. Se formularon cuatro dietas experimentales isoproteicas con niveles de inclusión de 0% (control), 12%, 22% y 32% de harina de grillo, las cuales fueron administradas durante ocho semanas a juveniles de L. vannamei alimentados tres veces al día, a las 06:00, 12:00 y 17:00 horas, con una ración equivalente al 5% de su biomasa. Se evaluaron semanalmente los parámetros de crecimiento (peso y longitud) y se calculó el valor de K por individuo. Los resultados indicaron que el crecimiento en peso y talla se vio afectado por condiciones subóptimas, como la alta densidad de cultivo (70 organismos/m²) y la disminución progresiva de la temperatura, actuando ambos como factores limitantes en todos los tratamientos. Aunque el tratamiento con 32% de inclusión (TR3) presentó valores de K ligeramente más altos y estables, no se observaron diferencias estadísticamente significativas respecto al control, lo que limita la evidencia sobre un efecto fisiológico positivo atribuible al uso de Acheta domesticus. En consecuencia, se concluye que, si bien esta harina representa una fuente proteica funcional y con perfil nutricional adecuado, su inclusión en dietas acuícolas no mejoró significativamente el desempeño fisiológico ni productivo bajo las condiciones evaluadas, por lo que se recomienda su aplicación únicamente en sistemas que garanticen condiciones óptimas de cultivo.
Keywords: ACUICULTURA SOSTENIBLE; CAMARÓN BLANCO DEL PACIFICO; ACHETA DOMESTICUS; CRECIMIENTO